2017
DOI: 10.5935/abc.20170023
|View full text |Cite
|
Sign up to set email alerts
|

A Single Resistance Exercise Session Improves Aortic Endothelial Function in Hypertensive Rats

Abstract: BackgroundPhysical exercise is an important tool for the improvement of endothelial function.ObjectiveTo assess the effects of acute dynamic resistance exercise on the endothelial function of spontaneously hypertensive rats (SHR).MethodsTen minutes after exercise, the aorta was removed to evaluate the expression of endothelial nitric oxide synthase (eNOS), phosphorylated endothelial nitric oxide synthase (p-eNOS1177) and inducible nitric oxide synthase (iNOS) and to generate concentration-response curves to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…It is also suggested that the stimulation of NO production is dependent on the volume of exercise, and a greater demand of oxygen and nutrients is involved in the beneficial effects of exercise on the endothelium [ 263 , 266 ]. Moreover, similar results are observed in hypertensive rats that single session of resisted exercise activates eNOS and promotes vasorelaxation [ 267 ]. Interestingly, expression of the prooxidant enzyme, NADPH oxidase, is reduced by exercise training in hypertensive rats, which may have a beneficial effect on the half-life of NO in the vascular wall [ 266 ].…”
Section: Physical Exercisesupporting
confidence: 75%
“…It is also suggested that the stimulation of NO production is dependent on the volume of exercise, and a greater demand of oxygen and nutrients is involved in the beneficial effects of exercise on the endothelium [ 263 , 266 ]. Moreover, similar results are observed in hypertensive rats that single session of resisted exercise activates eNOS and promotes vasorelaxation [ 267 ]. Interestingly, expression of the prooxidant enzyme, NADPH oxidase, is reduced by exercise training in hypertensive rats, which may have a beneficial effect on the half-life of NO in the vascular wall [ 266 ].…”
Section: Physical Exercisesupporting
confidence: 75%
“…Among the studied phosphorylation of eNOS sites, Thr495 and Serine 114, 615 and 633, the phosphorylation of Ser1177 or Thr495 is particularly important [38]. Although there has been debate about the role of Thr495 phosphorylation about NOS activity [22,23], the role of Ser1177 phosphorylation has been relatively well established as a positive post-translational modification for NOS activity [39]. Here, in the presence of mulberry, the phosphorylation of Thr495 and Ser1177 rather increased, enhancing NO release, consistent to a recent study of mulberry [11].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and dose–response meta-analysis showed that resistance exercise training improves endothelial function and that greater frequency, rather than intensity, is the key factor to maximize improvement in flow-mediated dilation 34 ; per opposition to the chronic effects, the acute effects of resistance exercise on endothelial function are not consensual. Some evidence has shown that acute high-intensity resistance eccentric exercise 35 may decrease endothelial function, whereas dynamic submaximal resistance exercise seems to acutely improve endothelial function in hypertensive rats 36 , 37 , type 2 diabetes patients 38 and healthy males 39 .…”
Section: Discussionmentioning
confidence: 99%